Illness Experience of Glaucoma Patients. - Hyeon ae Lee; Seon Nyeo Kim; Hwa Young Kim; Sue Kyung Sohn (Research in Community & Public Health Nursing (RCPHN), 2024)
Purpose: The purpose of this study was to understand and describe the experiences of patients with glaucoma. Methods: Data were collected from March to April in 2023, through individual in-depth interviews with 10 glaucoma patients. Verbatim transcripts were analyzed using Colaizzi's phenomenological analysis. Results: Six theme clusters were extracted that described patients' experiences: 1) The frightening disease unexpectedly discovered; 2) A dismal life gradually trapped in darkness; 3) Fear of the unseen; 4) Following treatment without any other options; 5) Grateful for the help but feeling miserable; 6) Realizing the importance of eyes and health. Conclusion: The results of this study provide a deep understanding and insight into the experience of Glaucoma patients. Glaucoma patients experienced physical, mental, and social pain through the disease process. Therefore, psychological nursing interventions are needed to understand and reduce mental pain along with medical treatment to relieve physical symptoms in glaucoma patients. Furthermore, it will be necessary to prepare institutional support measures to minimize various social restrictions.